Investigation and optimisation of the functioning parameters of the milking machine electronic unit, diagnosing the state of the udder quarters of cows for mastitis - P. A. Sаvinyh; A. A. Rylov; V. N. Shulatiev; S. A. Ivanovs (Аграрная наука Евро-Северо-Востока)
The article informs on the search of values of setting the parameters of electronic unit of the milking machine providing the current control of physiological state of udder quarters during milking. The milking machine is equipped with electrode sensor for quarterly control of the lactation intensity. A rotatable plan was used in the studies on a hexagon for two factors. The influence of delay duration of measuring and the duration of search for maximum on relative values of average yaver and maximum ymax deviations from minimum voltage value at the lower voltage divider arm has been determined. The algorithm of the program for the functioning of the electronic unit provided for restrictions on the width ∆ = 0.03 s and height Un = 2.45 V of the lactation diagram. There were experimentally determined the values of the duration of the measurement delay 10 s and the duration of the search for the maximum 40 s, which ensure an adequate quarterly indication of mastitis during milking. The threshold for changing the colour of the LEDs of the electronic unit from green to red, signalling inflammation of the mammary gland in the quarters, is set to exceeding ymax > 5 %. Parallel samples of milk from the udder quarters for the kenotest confirmed the efficiency of application and expediency of the milking machine, performing the function of quarterly testing of the quarters for mastitis. Providing the option of quarterly control of udder quarters by milking machine does not need correction of the basic circuit of electronic unit and is achieved only by its programming considering physiological features of livestock kept. The results of investigations indicate that, on average, for healthy cows, the range of variation of the maximum relative voltage deviation on the lower divider of the electronic unit should not exceed 6...10 %.